2005
DOI: 10.1093/ps/84.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of sodium bentonite as a detoxifier of broiler feed contaminated with aflatoxin and fumonisin

Abstract: Sodium bentonite (SB) was evaluated for its ability to reduce the deleterious effects of fumonisin B1 (FB1) and aflatoxin B1 (AFB1) in broiler diets. It was incorporated into the diets (0.3%) containing 2.5 mg/kg AFB1, 200 mg/kg FB1, or a combination of 2.5 mg/kg AFB1 and 200 mg/kg FB1. Aflatoxin B1 significantly diminished body weight gain, whereas FB1 or the combination of FB1 and SB had no effect. Addition of SB in the diets significantly diminished the inhibitory effects of dietary AFB1. Feeding AFB1 alone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
75
1
8

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(95 citation statements)
references
References 34 publications
7
75
1
8
Order By: Relevance
“…When compared to negative control, the preventive efficacy of 1.5% and 3% SB in aflatoxin containing diet was not significant (groups 3, 4) in contrast to the results of other authors reporting a significant amelioration after addition of SB to the diet containing aflatoxin (200 to 2500 ppb) (6,13,15). The beneficial effect of SB in above studies might be attributed to its sequestration action against aflatoxin in feeds based on the mechanism of adsorption and decrease in the aflatoxin bioavailability in the gastrointestinal tract.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…When compared to negative control, the preventive efficacy of 1.5% and 3% SB in aflatoxin containing diet was not significant (groups 3, 4) in contrast to the results of other authors reporting a significant amelioration after addition of SB to the diet containing aflatoxin (200 to 2500 ppb) (6,13,15). The beneficial effect of SB in above studies might be attributed to its sequestration action against aflatoxin in feeds based on the mechanism of adsorption and decrease in the aflatoxin bioavailability in the gastrointestinal tract.…”
Section: Discussioncontrasting
confidence: 75%
“…Zeolites (12,16), bentonites (7,11,26), and yeast/esterified glucomannan (1,4,6,15) were opted for because of their effect on reducing aflatoxin absorption from the gastrointestinal tract. Some studies have showed that the best method for decontamination is biological degradation by yeast and yeast components, which can remove aflatoxin under mild conditions, without using harmful chemicals or causing noticeable losses in nutritive value and palatableness of the feed (21,30).…”
Section: Introductionmentioning
confidence: 99%
“…implica que essas aves estavam desenvolvendo um comprometimento hepático, pois Harvey et al (1988) e Miazzo et al (2005) relataram, respectivamente, alterações histológicas, como fibrose interlobular e vacuolização citoplasmática peritubular, no fígado de aves com aflatoxicose e, conforme explica Fudge (2000), um fígado em estágio final, como na severa fibrose ou lipidose, pode produzir pouco extravasamento hepatocelular, o que resulta em níveis normais ou diminuídos de AST.…”
Section: Resultsunclassified
“…Nesses mesmos tratamentos, também não houve a diminuição da AST, o que comprova o efeito protetor desse adsorvente sobre as alterações no tecido hepático, produzidas pela aflatoxina, resultado que concorda com Miazzo et al (2005), que observaram redução da incidência e da severidade das alterações histopatlógicas, em aves que receberam aflatoxina e montmorilonita sódica associadas.…”
Section: Resultsunclassified
“…Os sinais da intoxicação por aflatoxinas depende principalmente de sua concentração no alimento, do tipo de aflatoxina e do tempo de ingestão (DOERR et al, 1983;OGIDO et al, 2004), sendo caracterizada pela imunodepressão, e por anomalias ósseas, hemorragias, despigmentação e alterações na função hepática (DOERR & HAMILTON, 1981;QUEZADA, 2000;ROSA et al, 2001;MIAZZO et al, 2005).…”
Section: Introductionunclassified